Discover new perspectives and gain insights with IDNLearn.com. Join our community to receive prompt and reliable responses to your questions from experienced professionals.
Sagot :
To find the minimum value for the equation [tex]\( 2x^2 - 4x - 2 = 0 \)[/tex], we need to complete the square.
First, let's start by dividing the entire equation by 2 to simplify the process:
[tex]\[ x^2 - 2x - 1 = 0 \][/tex]
Next, we'll complete the square for the expression [tex]\( x^2 - 2x \)[/tex]. To do this, we take half of the coefficient of [tex]\( x \)[/tex], which is [tex]\(-2\)[/tex], then we square it:
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
Now, we add and subtract this square within the equation:
[tex]\[ x^2 - 2x + 1 - 1 - 1 = 0 \][/tex]
[tex]\[ (x - 1)^2 - 2 = 0 \][/tex]
Rearranging, we get:
[tex]\[ (x - 1)^2 - 2 = 0 \][/tex]
Next, let's consider the options provided:
1. [tex]\( 2(x-1)^2 = 4 \)[/tex]
2. [tex]\( 2(x-1)^2 = -4 \)[/tex]
3. [tex]\( 2(x-2)^2 = 4 \)[/tex]
4. [tex]\( 2(x-2)^2 = -4 \)[/tex]
We need to match our derived equation to one of the given forms. From our work, we see:
First, consider:
[tex]\[ 2(x - 1)^2 = 4 \][/tex]
[tex]\[ (x - 1)^2 = 2 \][/tex]
This does not match our equation.
Second, consider:
[tex]\[ 2(x - 1)^2 = -4 \][/tex]
[tex]\[ (x - 1)^2 = -2 \][/tex]
This does not match our equation.
Third, consider:
[tex]\[ 2(x - 2)^2 = 4 \][/tex]
[tex]\[ (x - 2)^2 = 2 \][/tex]
This does not match our equation.
Fourth, consider:
[tex]\[ 2(x - 2)^2 = -4 \][/tex]
[tex]\[ (x - 2)^2 = -2 \][/tex]
This does not match our equation.
It turns out upon reflection that we should simplify and correctly identify the transformation.
The correct transformation from our working should be:
[tex]\[ 2(x - 1)^2 = -4 \][/tex]
Therefore, out of the given options, the correct equation that reveals the minimum value is:
[tex]\[ \boxed{2(x-1)^2 = -4} \][/tex]
First, let's start by dividing the entire equation by 2 to simplify the process:
[tex]\[ x^2 - 2x - 1 = 0 \][/tex]
Next, we'll complete the square for the expression [tex]\( x^2 - 2x \)[/tex]. To do this, we take half of the coefficient of [tex]\( x \)[/tex], which is [tex]\(-2\)[/tex], then we square it:
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
Now, we add and subtract this square within the equation:
[tex]\[ x^2 - 2x + 1 - 1 - 1 = 0 \][/tex]
[tex]\[ (x - 1)^2 - 2 = 0 \][/tex]
Rearranging, we get:
[tex]\[ (x - 1)^2 - 2 = 0 \][/tex]
Next, let's consider the options provided:
1. [tex]\( 2(x-1)^2 = 4 \)[/tex]
2. [tex]\( 2(x-1)^2 = -4 \)[/tex]
3. [tex]\( 2(x-2)^2 = 4 \)[/tex]
4. [tex]\( 2(x-2)^2 = -4 \)[/tex]
We need to match our derived equation to one of the given forms. From our work, we see:
First, consider:
[tex]\[ 2(x - 1)^2 = 4 \][/tex]
[tex]\[ (x - 1)^2 = 2 \][/tex]
This does not match our equation.
Second, consider:
[tex]\[ 2(x - 1)^2 = -4 \][/tex]
[tex]\[ (x - 1)^2 = -2 \][/tex]
This does not match our equation.
Third, consider:
[tex]\[ 2(x - 2)^2 = 4 \][/tex]
[tex]\[ (x - 2)^2 = 2 \][/tex]
This does not match our equation.
Fourth, consider:
[tex]\[ 2(x - 2)^2 = -4 \][/tex]
[tex]\[ (x - 2)^2 = -2 \][/tex]
This does not match our equation.
It turns out upon reflection that we should simplify and correctly identify the transformation.
The correct transformation from our working should be:
[tex]\[ 2(x - 1)^2 = -4 \][/tex]
Therefore, out of the given options, the correct equation that reveals the minimum value is:
[tex]\[ \boxed{2(x-1)^2 = -4} \][/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.